2016
DOI: 10.5194/acp-16-7559-2016
|View full text |Cite
|
Sign up to set email alerts
|

Strong modification of stratospheric ozone forcing by cloud and sea-ice adjustments

Abstract: Abstract. We investigate the climatic impact of stratospheric ozone recovery (SOR), with a focus on the surface temperature change in atmosphere-slab ocean coupled climate simulations. We find that although SOR would cause significant surface warming (global mean: 0.2 K) in a climate free of clouds and sea ice, it causes surface cooling (−0.06 K) in the real climate. The results here are especially interesting in that the stratosphere-adjusted radiative forcing is positive in both cases. Radiation diagnosis sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
5
15
0
Order By: Relevance
“…This is consistent with the less significant temperature changes in JJA and SON. It has been suggested that the lower-stratospheric warming, due to ozone recovery, enhances static stability and reduces relative humidity in the upper troposphere and near the tropopause, and both contribute to cloud decreases (Jenkins, 1999;Yang et al, 2012;Xia et al, 2016Xia et al, , 2018. From Fig.…”
Section: Cloud Response To Ozone Recoverymentioning
confidence: 95%
“…This is consistent with the less significant temperature changes in JJA and SON. It has been suggested that the lower-stratospheric warming, due to ozone recovery, enhances static stability and reduces relative humidity in the upper troposphere and near the tropopause, and both contribute to cloud decreases (Jenkins, 1999;Yang et al, 2012;Xia et al, 2016Xia et al, , 2018. From Fig.…”
Section: Cloud Response To Ozone Recoverymentioning
confidence: 95%
“…3b ). The change of the net radiative fluxes at TOA is decomposed into the instantaneous radiative effect of the dust and radiative feedbacks consisting of the water vapor, cloud, albedo, and temperature feedbacks 25 , 26 (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, rapid adjustments lead to the ERF for black carbon (BC) being half that of its IRF (Stjern et al, 2017;Smith et al, 2018). On the other hand, Xia et al (2016) found that cloud and sea ice feedbacks driven by stratospheric O3 recovery included in the ERF definition lead to a significant adjustment that changes the sign and magnitude of the stratospheric O3 forcing from the SARF. Although the definitions of RF and ERF differ in where the change in radiative fluxes is diagnosed, ERFs at the tropopause are nearly identical to those at the TOA for tropospheric forcing agents; this is also the case for SARFs.…”
Section: Introductionmentioning
confidence: 99%